2014
DOI: 10.1136/postgradmedj-2013-132486
|View full text |Cite
|
Sign up to set email alerts
|

Gamification as a tool for enhancing graduate medical education

Abstract: IntroductionThe last decade has seen many changes in graduate medical education training in the USA, most notably the implementation of duty hour standards for residents by the Accreditation Council of Graduate Medical Education. As educators are left to balance more limited time available between patient care and resident education, new methods to augment traditional graduate medical education are needed.ObjectivesTo assess acceptance and use of a novel gamification-based medical knowledge software among inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
159
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(174 citation statements)
references
References 15 publications
2
159
0
7
Order By: Relevance
“…At university level, 1 study has reported results involving graduate students (Nevin et al, 2014), while at K-12 level, 3 studies have reported results involving elementary school students (Boticki, Baksa, Seow, & Looi, 2015;Simoes, Mateus, Redondo, & Vilas, 2015; , 2 studies have reported results involving middle school students (Attali & Arieli-Attali, 2015;Long & Aleven, 2014 ) and 2 studies have reported results involving high school students (Davis & Klein, 2015;Paiva, Barbosa, Batista, Pimentel, & Bittencourt, 2015). A possible explanation of this disproportion is that perhaps it is easier for college instructors to experiment with using gamification in their own courses.…”
Section: What Educational Level Is Targeted?mentioning
confidence: 74%
See 2 more Smart Citations
“…At university level, 1 study has reported results involving graduate students (Nevin et al, 2014), while at K-12 level, 3 studies have reported results involving elementary school students (Boticki, Baksa, Seow, & Looi, 2015;Simoes, Mateus, Redondo, & Vilas, 2015; , 2 studies have reported results involving middle school students (Attali & Arieli-Attali, 2015;Long & Aleven, 2014 ) and 2 studies have reported results involving high school students (Davis & Klein, 2015;Paiva, Barbosa, Batista, Pimentel, & Bittencourt, 2015). A possible explanation of this disproportion is that perhaps it is easier for college instructors to experiment with using gamification in their own courses.…”
Section: What Educational Level Is Targeted?mentioning
confidence: 74%
“…Another interesting observation is the low proportion of studies on gamifying STEM disciplines, excluding CS/IT and mathematics, where reinforcement of motivation is particularly beneficial: only two out of thirty two (Bonde et al, 2014) and . Anderson, Nash, & McCauley, 2015;Auvinen, Hakulinen, & Malmi, 2015;Bernik, Bubaš, & Radošević, 2015;Hakulinen, Auvinen, & Korhonen, 2015;Herbert, Charles, Moore, & Charles, 2014;Ibanez, Di Serio, & Delgado-Kloos, 2014;Knutas, Ikonen, Maggiorini, Ripomonti, & Porras, 2014a;Knutas, Ikonen, Nikula, & Porras, 2014b;Krause, Mogalle, Pohl, & Williams, 2015;Laskowski & Badurowicz, 2014;Leach, Laur, Code, Bebbington, & Broome, 2014;Lehtonen, Aho, Isohanni, & Mikkonen, 2015;Poole, Kemp, Patterson, & Williams, 2014;Sillaots, 2014;Sillaots, 2015;Smith, Herbert, Kavanagh, & Reidsema, 2014;Tvarozek & Brza, 2014) Math 5 (10%) (Attali & Arieli-Attali, 2015 a ;Christy & Fox, 2014;Long & Aleven, 2014;Paiva et al, 2015 a ; Pedro, Lopes, Prates, Vassileva, & Isotani, 2015b) a Multimedia/ Communication 6 (12%) (Barata, Gama, Jorge, & Gonçalves, 2014;Hanus & Fox, 2015;Holman et al, 2015;Jang, Park, & Yi, 2015;Leach et al, 2014;Utomo & Santoso, 2015) Medicine/Biology/ Psychology 5 (10%) (Bonde et al, 2014;Landers & Landers, 2015;Nevin et al, 2014;Pettit, McCoy, Kinney, & Schwartz, 2015; a Languages 4 (8%) ...…”
Section: What Subjects Are Gamified?mentioning
confidence: 99%
See 1 more Smart Citation
“…While there has been much interest expressed in the use of serious games and gamification of eLearning tools (Ahmed et al, 2015;McCoy, Lewis, & Dalton, 2016;Nevin et al, 2014;(Graafland, Schraagen, & Schijven, 2012), we note that there has been little actual activity in this area. Graafland et al only found 30 examples of serious games in a systematic review and noted that most of these were not validated as educational tools.…”
Section: Discussionmentioning
confidence: 99%
“…The game Kaizen, a term meaning continuous learning, was developed in by James Willig, MD as a way to supplement learning for medical residents (Nevin et al, 2014). The Kaizen software delivers questions online in a game format, generating competition among participants.…”
mentioning
confidence: 99%